Liver Transcriptome and Gut Microbiome Analysis Reveals the Effects of High Fructose Corn Syrup in Mice - Shen, Yu; Sun, Yangying; Wang, Xiaoli; Xiao, Yingping; Ma, Lingyan; Lyu, Wentao; Zheng, Zibin; Wang, Wen; Li, Jinjun (Frontiers in Nutrition, 2022)
Lipid metabolism is closely related to metabolic diseases such as obesity and diabetes. High fructose corn syrup (HFCS) is a syrupy mixture of glucose and fructose, which reported to cause abnormal increases in body fat and alter the structure and abundance of gut microbes in the long term. In this study, mice were fed without or with high fructose corn syrup in drinking water, which labeled as group C (n=5) and group H (n=5), respectively. Liver and colonic content samples were selected from two groups for high-throughput transcriptome sequencing and 16SrRNA sequencing respectively, to explore the effect of high fructose corn-syrup in hepatic lipid metabolism and colon microbes. Our results indicated that the expression of gene Elovl3 reduced while the other genes, including Scd1, Pparg, Fads2, Acot2, Acot3, Acot4, Fabp2 were all up-regulated in the H group. Meanwhile, we thoroughly investigated the mice colon microbiota by 16SrRNA sequencing and analyzed the correlation of gene with the colon microbiota. Our results indicated that compare with group C, the abundance of Bacteroidetes is increase, Firmicutes and the Firmicutes/Bacteroidetes ratio is decrease in group H. At the genus level, the relative abundance of Bifidobacterium, Lactobacillus, Faecalibaculum, Erysipelatoclostridium and Parasutterella was increased. On the contrary, Staphylococcus, Peptococcus, Parabacteroides, Donghicola and Turicibacter was reduced. Pparg, Acot2, Acot3 were positive correlations to Erysipelatoclostridium and negative correlations to Parabacteroides, Staphylococcus and Turicibacter. Bifidobacterium is negative correlations to Elovl3. Overall, HFCS affects hepatic lipid metabolism and alters gut microbiota, our study provide a solid theoretical and practical basis for the role of microbiota in the regulating lipid metabolism in the future.